An economic feasibility study of a managed supply chain stocker operation in NE Oklahoma - Johnstone, Sean (Kansas State University, 2024)
Oklahoma is traditionally known for stocker cattle, but in the northeastern corner of the state, the practice of grazing yearlings is relatively rare. “Green Country” is a patchwork of small ranches, mostly in cow-calf production and predominantly with cow herds less than 50. These producers have limited options when it comes to marketing their calves and are tied to the use of local auctions by their size. These cattlemen represent an opportunity to a stocker producer. The region’s improved grass pastures are capable of withstanding heavy grazing pressure if managed properly, there is a ready supply of calves, and potential feeder cattle buyers are nearby in western TX, OK and KS. By purchasing calves from a select group of local producers, a consistent group of high-quality calves could be obtained annually from within just a few miles of the new operation, easing the logistics, health concerns and potential quality issues in buying from several local auctions. The cow-calf producers will get a competitive price for their calves, save on commission fees, and reduce pricing risk by avoiding the sale barn. Calves purchased into the program would be subject to requirements as far as quality, phenotype, and condition. If done properly the group should represent an approximation of a single large ranch’s calf crop. The calves would be purchased in two blocks, one winter and one summer. The calves will rotationally graze sod-seeded small grains or improved grass pastures in the winter and summer respectively. These practices will reduce health risk and increase efficiency. The scale of the business will offer increased marketing channels, with particular focus on forward contracting direct to buyers. Historical price analysis was completed as part of the research for this project and serves to show the volatility of the stocker segment. Over 10 years, pricing trends are loose at best, allowing only general observations. The best barometer for performance year over year was the Value of Gain. If the Unit Cost of Production (UCOP) is known for a given period, it can be directly compared to the Value of Gain (VOG); if the UCOP is higher than the VOG, the cattle will not make money. Ideally, actual margins would have been analyzed but the differences between stocker operations make this an impossible task. There is too much variation from ranch to ranch to confidently use such findings, even if the source data could be found. Enterprise budgets were developed to forecast profitability of the businesses and indicated that in 2023-24, the business would have shown a net profit of $74,604 for the two groups of calves. Return on investment in this case was roughly 8.7% with all costs included. Risks associated with the business are much the same as any other stocker business, though the proposed business is designed to mitigate as many as possible, favoring lower risk over the opportunity for higher returns. Some years, the business is profitable. On years with thin margins, the operational methods or throughput may need to be adjusted to maintain profitability. Overall, the business design should be profitable in a wider range of market conditions than a traditional grazing operation. Observation of the markets, and an understanding of the cattle cycle is critical to the long-term success of the proposed business.
Keywords: Stocker cattle; Feasibility; Supply chain; Oklahoma